2017
DOI: 10.3390/su9081308
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Techniques for Urban Heating Analysis: A Case Study of Sustainable Construction at District Level

Abstract: Abstract:In recent years, many new districts in urban centres have been planned and constructed to reshape the structure and functions of specific areas. Urban regeneration strategies, planning and design principles have to take into account both socioeconomic perspectives and environmental sustainability. A district located in the historical city centre of Terni (Italy), Corso del Popolo, was analysed to assess the construction effects in terms of surface urban heat island (SUHI) mitigation. This district is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Surface and air UHI differences and the timing of their peaks depend on the urban and rural surface properties (e.g., moisture, aerodynamic roughness, albedo, emissivity, and thermal admittance), season, geography, and prevailing weather conditions [29,192]. Schwarz et al [20] carried out a campaign in Leipzig, Germany, providing LST from airborne flights and air temperature (T air ) from weather stations and a mobile traverse.…”
Section: Relationship Between Surface and Air Uhismentioning
confidence: 99%
“…Surface and air UHI differences and the timing of their peaks depend on the urban and rural surface properties (e.g., moisture, aerodynamic roughness, albedo, emissivity, and thermal admittance), season, geography, and prevailing weather conditions [29,192]. Schwarz et al [20] carried out a campaign in Leipzig, Germany, providing LST from airborne flights and air temperature (T air ) from weather stations and a mobile traverse.…”
Section: Relationship Between Surface and Air Uhismentioning
confidence: 99%
“…Factors related to the urban texture at district level that affect the SUHI phenomenon-driving the heat trapping and absorption-rely on surface albedo, material, and color; on building layout, slope, and height; and on greenery cover [51][52][53][54]. At the same time, the urban texture can intensify the warming effect by reducing the wind circulation [55].…”
Section: Yearly Trend Of Suhi Footprint and Magnitudementioning
confidence: 99%
“…The UHI is rather weak in the daytime, but it becomes more pronounced after sunset. Under some specific conditions, studies have found that some relevant factors (e.g., urban geometry, thermal admittance, and moisture) were important control factors for the UHI intensity [18][19][20]. Remote sensors such as the Landsat TM/ETM+/TIRS and Moderate Resolution Imaging Spectroradiometer (MODIS) play important roles in SUHI research [21].…”
Section: Introductionmentioning
confidence: 99%